A EDUCAÇÃO DA CRIANÇA DE 0 A 6 ANOS NO MUNICÍPIO DE PONTA GROSSA: FUNDAÇÃO PROAMOR - Prestes, Reulcinéia Isabel (2008)
This study focuses the trajectory of care about child on its zero to six years old into PROAMOR Foundation in Ponta Grossa State of Paraná. The local and national policies were analyzed to observe the actions coming from them toward to child. The historic, social, economic, political and cultural aspects were considered through the child context caring. The understanding about the conceptions and theories that provided support to the actions to child offered reference to analyze the period focused – 1987 a 2000 in the Foundation. It searched to rescue the history of Foundation raising to the articulation the caring of child by the Educational Department as the Brazilian legal determination Lei de Diretrizes e Bases nº 9.394/96. It was organized a theoretical frame to point the actions and policies around the child and childhood. The analysis had the micro and macro system as model into PROAMOR Foundation. Also the research showed the distance between children’s desires and the work provided by the PROAMOR Foundation.